PENYULUHAN FAKTOR YANG MEMPENGARUHI KEJADIAN PEREMPUAN PREEKLAMPSI HAMIL DI BIDANG RUMAH SAKIT SEMBIRING DELI TUA - Junita Ika Susanti; Amelia Sarma; Nora Ervina Sembiring; Evalina Manurung (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Pregnancy is the result of a fetus from conception to birth. Pregnancy is divided into 3 trimester first trimester begins from conception to 3 months, the second quarter from the fourth month to 6 months, the third quarter of the seventh month to 9 months. From the results of the initial survey conducted at the General Hospital SEMBIRING field, the data obtained in November 2013, the number of pregnant women who come to the RSU. SEMBIRING Field 40 people. And after investigation of 40 pregnant women who come to the RSU. SEMBIRING there are pregnant women who have preeklampsi. This type of study is a descriptive cross sectional analytic approach. This research was conducted at The Hospital. SEMBIRING Deli Tua. Samples used in this study is the total sampling, which in this technique the researchers took the overall population to be sampled, as many as 30 people. Data were analyzed for bivariate calculations in this study using the chi-square ( x ^2 ) at the 95% significance level ( α : 5 % ). Results of studies using Chi-square test at p = 0.012 < 0.05 means that there is a relationship of parity with the influence signifiaknpreeklampsi. Results of studies using Chi-square test at p = 0.003<0.05 means that there is a correlation with gestational age influence signifiaknpreeklampsi the results of research using Chi-square test at p = 0.012 < 0.05 means that there is a relationship signifiakn influence the occurrence of disease history preeklampsi. Results of studies using Chi-square test at p = 0.001 < 0.05 means that there is a genetic influence signifiakn relationship with the RSU SEMBIRINGpreeklampsi in Deli Tua. The conclusion of this study that preeklampsi occurred in the life of the mother occurred because of parity, gestational age, medical history, genetic, SEMBIRING Hospital in Deli Tua.